Internalisasi kesantunan berbahasa siswa MI melalui game edukasi berbasis kearifan lokal Temanggung - Ibda, Hamidulloh; Hilmi, Muhammad Naufal; Agustina, Ayu Rahma (Al-Azkiya: Jurnal Pendidikan MI/SD, 2023)
This research is motivated by the lack of game development in Indonesian language learning based on local wisdom to instill language politeness in elementary school students. This research aims to reveal the needs of students and teachers for developing educational games based on Temanggung local wisdom in instilling language politeness in elementary school students. The method used was quantitative through a survey with a cross-sectional survey type. The research findings refer to 23 students and 23 teachers, obtained data on student needs for the development of educational games based on Temanggung local wisdom to instill language politeness in elementary school students from the 20 categories obtained the conclusion that they need the most critical details in each aspect, because of the 20 aspects, in the category of high need there are 19 aspects, enough need one aspect, and less need 0 aspects. Meanwhile, in the teacher's need for the development of educational games based on Temanggung local wisdom to instill language politeness in elementary school students, data from the 20 categories were obtained, in the category of high need getting the highest 12, the category of moderate need the highest 9, and less need the highest 0. Regarding teacher needs for training in making visual novel games, the same score is obtained, namely the category of high need 10 teachers (43.5%) and quite need 10 teachers (43.5%). The results of the analysis of the needs of students and teachers recommend the development of educational games based on Temanggung local wisdom to instill language politeness in elementary school students because the needs of students get the most 19 scores, and the needs of teachers get the most 12 scores out of 20 aspects.